2014
DOI: 10.1107/s1399004714018446
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron scattering reveals the assembly mode and oligomeric architecture of TET, a large, dodecameric aminopeptidase

Abstract: The present work illustrates that small-angle neutron scattering, deuteration and contrast variation, combined with in vitro particle reconstruction, constitutes a very efficient approach to determine subunit architectures in large, symmetric protein complexes. In the case of the 468 kDa heterododecameric TET peptidase machine, it was demonstrated that the assembly of the 12 subunits is a highly controlled process and represents a way to optimize the catalytic efficiency of the enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…S5) compatible with dodecameric topology, pointing toward the simultaneous occurrence of multiple assembly pathways. These results are corroborated with an analysis of TET2/TET3 heterododecamer using small-angle neutron scattering, where both the productive assembly octamer and horseshoe hexamers were detected ( 28 ). The apparent discrepancy between the studies using the native and the mutant TET2 sequences suggests that the mutation introduced at the trimerization interface may have substantially altered self-organization.…”
Section: Discussionsupporting
confidence: 67%
“…S5) compatible with dodecameric topology, pointing toward the simultaneous occurrence of multiple assembly pathways. These results are corroborated with an analysis of TET2/TET3 heterododecamer using small-angle neutron scattering, where both the productive assembly octamer and horseshoe hexamers were detected ( 28 ). The apparent discrepancy between the studies using the native and the mutant TET2 sequences suggests that the mutation introduced at the trimerization interface may have substantially altered self-organization.…”
Section: Discussionsupporting
confidence: 67%
“…In Pyrococcus horikoshii, four TET-aminopeptidases -PhTET1, PhTET2, PhTET3, and PhTET4 -have been described and each of them displays a different substrate specificityaspartyl-, leucyl-, lysyl-, and glycyl-aminopeptidase activity, respectively (15)(16)(17)(18). Remarkably, heterocomplexes, made of PhTET2 and PhTET3, have been reported, leading to the assumption of the peptidasome particle existence (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have recently demonstrated that the TET peptidase oligomerization process is not random and involves the formation of hexameric intermediates (Appolaire et al, 2013). In the case of the in vitro reconstructed PhTET2:PhTET3 dodecameric particles, the use of SANS and contrast variation revealed that this controlled oligomerization process results in the obligatory formation of catalytic chambers made of the combination of the two different active sites (Appolaire et al, 2014). Thus, after cleavage, the free N-terminus of the polypeptidic product can be easily redirected towards the most suitable active site with respect to the identity of its P1 amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the stoichiometry of one sample could be assessed based on the properties of in vitro reconstituted hetero-oligomers that were produced in order to study the TET oligomerization process. In these studies, the hetero-oligomeric TET particles containing PhTET2 and PhTET3 were obtained by mixing the dimeric precursors recovered after EDTA and basic pH treatment in a re-assembling buffer containing cobalt (Appolaire et al, 2014). The different heterooligomeric forms were purified to homogeneity in enough amounts to be analysed by small angle neutron scattering (SANS).…”
Section: The Phtet2 and Phtet3 Proteins Can Form Hetero-oligomeric Domentioning
confidence: 99%
See 1 more Smart Citation